2017
DOI: 10.1177/1477370817749177
|View full text |Cite
|
Sign up to set email alerts
|

Coordination problems in cryptomarkets: Changes in cooperation, competition and valuation

Abstract: The new drug markets emerging on the dark net (TOR) have reduced earlier drug market risk factors such as visibility and violence. This study uses economic sociology and transaction cost economics to broaden the present understanding of cryptomarkets. Results focus on three coordination problems characterising illegal markets and how they are alleviated in cryptomarkets. More information and better visibility increase competition, the feedback system enforces cooperation and border control introduces a new cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 54 publications
(130 reference statements)
2
57
0
5
Order By: Relevance
“…For instance, within criminology, researchers have examined the effect of specific news on illicit sales volumes, finding counterintuitive increases in Dark Web transactions (Ladegaard 2019). Other criminology scholars have examined the structure of illicit digital markets, and the associated efficiency and resiliency they exhibit (Bakken, Moeller & Sandberg 2018;Duxbury & Haynie 2019). In a related IS study, Yue, Wang, & Hui (2019) conducted a user-generated content analysis of Dark Web hacker communities, and found evidence connecting increases in user chatter to a lower frequency of cyber-attacks.…”
Section: Research Examining Darknets and The Dark Webmentioning
confidence: 99%
“…For instance, within criminology, researchers have examined the effect of specific news on illicit sales volumes, finding counterintuitive increases in Dark Web transactions (Ladegaard 2019). Other criminology scholars have examined the structure of illicit digital markets, and the associated efficiency and resiliency they exhibit (Bakken, Moeller & Sandberg 2018;Duxbury & Haynie 2019). In a related IS study, Yue, Wang, & Hui (2019) conducted a user-generated content analysis of Dark Web hacker communities, and found evidence connecting increases in user chatter to a lower frequency of cyber-attacks.…”
Section: Research Examining Darknets and The Dark Webmentioning
confidence: 99%
“…Cryptomarket users have been most commonly young males who have decided to buy drugs online for safety reasons . Cryptomarkets often build trust systems that enable their functionality even in anonymity . The illegal sale of drugs is also seen on the clear web , which is less hidden than cryptomarkets but presents a challenge for law enforcement owing to the vast number of websites on the Internet.…”
Section: Introductionmentioning
confidence: 99%
“…A possible hypothesis could be their involvement at a high level in the distribution chain, supplying substances for distribution rather than consumption. As a consequence, cryptomarkets may also be a business-to-business market, which was also noted in (Aldridge & Décary-Hétu, 2014;Bakken et al, 2017;Cunliffe et al, 2019). Paquet-Clouston et al showed that only a small portion of vendors succeed in generating regular sales while the majority of vendors seems to be spectators with a limited number of sales (Paquet-Clouston et al, 2018).…”
Section: Countrymentioning
confidence: 93%
“…Five vendors stated that they produced their own products. Bakken et al, (Bakken et al, 2017) stated that direct contact with the manufacturer could mean that consumers purchasing from these vendors could receive more information about the drugs they are using which could, in turn, reduce the harm of drug use (Barratt et al, 2014;Van Hout & Bingham, 2013). Finally, products other than prescription drugs and medicine were also offered by 25% of vendors.…”
Section: Countrymentioning
confidence: 99%